The 2 March 2016 Wharton Basin Mw 7.8 earthquake: High stress drop north‐south strike‐slip rupture in the diffuse oceanic deformation zone between the Indian and Australian Plates. Issue 15 (4th August 2016) - Lay, Thorne; Ye, Lingling; Ammon, Charles J.; Dunham, Audrey; Koper, Keith D.
Abstract: The diffuse deformation zone between the Indian and Australian plates has hosted numerous major and great earthquakes during the seismological record, including the 11 April 2012 Mw 8.6 event, the largest recorded intraplate earthquake. On 2 March 2016, an Mw 7.8 strike‐slip faulting earthquake occurred in the northwestern Wharton Basin, in a region bracketed by north‐south trending fracture zones with no previously recorded large event nearby. Despite the large magnitude, only minor source finiteness is evident in aftershock locations or resolvable from seismic wave processing including high‐frequency P wave backprojections and Love wave directivity analysis. Our analyses indicate that the event ruptured bilaterally on a north‐south trending fault over a length of up to 70 km, with rupture speed of ≤ 2 km/s, and a total duration of 35 s. The estimated stress drop, 20 MPa, is high, comparable to estimates for other large events in this broad intraplate oceanic deformation zone. Key Points: The 2016 earthquake has little seismic wave directivity for an Mw 7.8 strike‐slip faulting event Aftershocks, surface waves, and finite fault inversions indicate north‐south rupture ≤70 km long The static stress drop is 20 MPa, a high value similar to other events in the intraplate deformation zone